Filio-parental violence analyzed through the Spanish press (2010–2020). Child-to-parent violence: A case of family violence - Martínez Torvisco, Juan; Wichrowska, Monika; Pellerone, Monica (Frontiers in Sociology, 2023)
Violence exercised by children to parents has increased significantly, affecting society both directly and indirectly. This violence is one of the least investigated and least exposed by the media. The aim of this work is to know how the media portrayed this problem. The qualitative methodology has been chosen for this study and a multidimensional analysis of journalistic and literary texts. The published news related to violence by children to parents are collected from 2010 to 2020 in the following Spanish newspapers: El País; ABC; El Día; El Mundo; La Vanguardia; El Periódico; La Provincia; Canarias 7; 20 Minutos; Diario de Avisos. The text corpus was subsequently analyzed with the open access software Iramuteq. The results show a total of 204232 words (number of occurrences), of which 4561 appear only once (number of Hapax). The words "violence", "father" and "son" are those that appear most frequently in the analysis of the texts and present a strong co-occurrence among them. As contributions, it should be noted that child-to-parent violence is described as a problem confined to the family environment. The importance of the preventive aspects of this violence within the family context would be shown in this paper.